Croatian EFL learners' affective profile, aspirations and attitudes to English classes - Mihaljević Djigunović, Jelena (Array, 2007)
The author focuses on affective learner characteristics as individual differences among Croatian learners of EFL. In the introduction to the paper she contextualizes affective aspects of FL learning by identifying those factors that are relevant for this paper and through referring to relevant second language acquisition and FL theory research studies. In the main part of the paper the author describes her own research carried out on a convenience sample of Croatian primary and secondary school learners of EFL. She considers the findings concerning their affective profile, aspirations and attitudes to EFL classes in interaction with a host of other variables shown important in FL learning, such as out-of-class learning of EFL, gender, school location, use of the Internet etc. She concludes that, besides their importance at the theoretical level, the obtained results have important practical implications, particularly for FL teacher education.